Tolerance in Kidney Transplantation: What Is on the B Side? - Laura Carreras-Planella; Francesc E. Borràs; Marcella Franquesa (Hindawi Limited, 2016)
Regulatory B cells (Breg) are in the spotlight for their role in immune homeostasis maintenance and tolerance achievement as in the last years the correlation with functional and increased Breg numbers in autoimmune diseases and transplantation has been extensively proven. Their study is, however, in its infancy with still little knowledge and consensus on their origin, phenotype, and mechanism of action. All this hampers the pursuit of an effective Breg induction method for therapeutic purposes. In this review we aim to summarize the studies on human Breg and their implication in kidney transplantation and to further discuss the issues surrounding therapeutic applications of this cell subset.